The Imperial War Museum book of the desert war - Gilbert, Adrian; Imperial War Museum (Great Britain) (London : Sidwick & Jackson in association with the Imperial War Museum, 1992)
The extracts from memoirs, diaries, letters and interviews reflect the experience of the campaign, from the noise and smoke of battle and the vagaries of desert life to leave spent in Cairo and Alexandria, the development of the Long Range Desert Group and the SAS, Rommel and the Afrika Corps.
Title on jacket: The Imperial War Museum book of the desert war, 1940-1942.
Includes bibliographical references.
Keywords: 1939-1945; World War, 1939-1945 -- Commando operations -- Africa, North; World War, 1939-1945 -- Campaigns -- Africa, North; Guerre mondiale, 1939-1945 -- z; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- Afrique du Nord; Commando troops; Military campaigns; North Africa